2017
DOI: 10.1080/03601234.2017.1316158
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide-induced disturbance of the redox balance in the chick embryonic brain

Abstract: This study was undertaken to determine the redox balance in the developing brain after exposure to acrylamide (ACR), a potent neurotoxin. The studies were performed using an in ovo chick embryo model. The antioxidant enzymes SOD, GPx, CAT, and reduced glutathione (GSH) were used as indicators of the redox balance. Eggs were injected with ACR doses of 40 mg kg egg mass (2.4 mg egg) on embryonic day 17 (E17). The activity of the antioxidant enzymes and the concentration of GSH were measured at E17, E18, and E19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Many studies have indicated that rats treated orally with ACR at 20 ~ 50 mg kg ‐1 day ‐1 can produce cumulative neurotoxicity, primarily exhibiting gait abnormality and brain injury (Allam, El‐Ghareeb, Abdul‐Hamid, Baikry, & Sabri, 2011; Batoryna et al., 2017; Pan et al., 2015; Spencer & Schaumburg, 1974; Venkataswamy et al., 2017). Table (4) shows the values of dopamine (DA) and noradrenaline (NA) in the blood serum and cerebral cortex region of male experimental rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have indicated that rats treated orally with ACR at 20 ~ 50 mg kg ‐1 day ‐1 can produce cumulative neurotoxicity, primarily exhibiting gait abnormality and brain injury (Allam, El‐Ghareeb, Abdul‐Hamid, Baikry, & Sabri, 2011; Batoryna et al., 2017; Pan et al., 2015; Spencer & Schaumburg, 1974; Venkataswamy et al., 2017). Table (4) shows the values of dopamine (DA) and noradrenaline (NA) in the blood serum and cerebral cortex region of male experimental rats.…”
Section: Resultsmentioning
confidence: 99%
“…Acrylamide (CH 2 = CHCONH 2 ) is an organic compound that is soluble in water and formed in food when exposed to high temperatures. Studies have shown that acrylamide is one of the causes of cancer, as well as affecting the brain and the natural balance of hormones in humans (Batoryna, Lis, & Formicki, 2017). Various studies have reported several harmful effects in experimental rats due to acrylamide administration, such as neuropathy, low tendon reflexes, muscle weakness, behavioral disorders, and toxic symptoms of the nervous system, such as tremors, convulsions paralysis, and multiple changes in levels of the neurotransmitter in different brain regions (Goudarzi et al., 2019; Zhang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that some neurotoxins (i.e. acrylamide) involve varied disturbances and defence responses in the antioxidative system of the chicken embryo's brain (Batoryna et al, 2017;2018).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, AA has been demonstrated to be neurotoxic in humans and laboratory animals [ 20 , 21 , 22 ], resulting in sensory and motor dysfunction, skeletal muscle weakness, weight loss, and ataxia [ 23 ]. One of the important mechanisms by which AA induces neurotoxicity is that it can destroy the redox balance and induce oxidative stress in neurons [ 24 , 25 ]. Under oxidative stress of AA, intracellular ROS were greatly produced, GSH levels decreased rapidly, and a series of oxidative stress followed [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOD, a metalloenzyme belong to antioxidant enzymes, detoxify oxidative stress through transforms the superoxide radical into hydrogen peroxide which was then degraded into water and oxygen by catalase and glutathione peroxidase [ 24 , 39 ]. The effect of AA on SOD activity in different experimental models has been reported in many previous studies, but the results seem to be inconsistent.…”
Section: Discussionmentioning
confidence: 99%